Impact and evolution of right ventricular dysfunction after successful MitraClip implantation in patients with functional mitral regurgitation. (June 2016) - Godino, Cosmo; Salerno, Anna; Cera, Michela; Agricola, Eustachio; Fragasso, Gabriele; Rosa, Isabella; Oppizzi, Michele; Monello, Alberto; Scotti, Andrea; Magni, Valeria; Montorfano, Matteo; Cappelletti, Alberto; et al.
Abstract: Background: Right ventricular dysfunction (RVdysf) is a predictor of poor outcome in patients with heart failure and valvular disease. The aim of this study was to evaluate the evolution and the impact of RVdysf in patients with moderate–severe functional mitral regurgitation (FMR) successfully treated with MitraClip. Methods and results: From October 2008 to July 2014, 60 consecutive high surgical risk FMR patients were evaluated and stratified into two groups: RVdysf group (TAPSE < 16 mm and/or S′TDI < 10 cm/s, 21 patients) and No-RVdysf group (38 patients). The overall mean age of patients was 73 ± 8 (83% male). Ischemic FMR etiology was present in 67%. Mean LVEF was 30 ± 10%. Overall mean time follow-up was 565 ± 310 days. The only significant difference between the two groups was a greater prevalence of stroke, ICD and use of aldosterone antagonist in RVdysf group. Acute procedural success was achieved in 90% of patients. At 6-month echo-matched analysis significant RV function improvement was observed in patients with baseline RVdysf (TAPSE 15 ± 3.0 vs. 19 ± 4.5, p = 0.007; S′TDI 7 ± 1.2 vs. 11 ± 2.8, p < 0.0001; baseline vs. 6-month, respectively). The mean improvement in the 6-min walking test was significant in both groups (120 and 143 m, RVdysf and No-RVdysf groups, respectively). At Kaplan–Meier analysis, the presence of RVdysf did not affect the outcome in terms of freedom from composite efficacy endpoint. Conclusions: This study shows that successful MitraClip implantation in patients with FMR and concomitant right ventricular dysfunction yields significant improvement of RV function at mid-term follow-up. Further data on larger population will be required to confirm our observations.